Inadimplemento eficiente nos contratos empresariais à luz do direito brasileiro atual - Fernando Vinicius Tavaraes Magalhaes Morais (2019)
The current paper examines the efficient breach theory of contracts, from the Common Law in the United States, according to which, briefly, the best available option for the debtor may be to breach the contract and this will occur when the costs of performance exceed the costs of thebreach. In such case the debtor will profit more and the creditor will not be worse off than if the contract were performed. The present goal is, in addition to presenting the theory, check the possibility of applying it in Brazil, focusing on contracts between companies. Therefore, thework is structured into introduction, three chapters of development and ends with the conclusion. After the introduction, which explains more deeply the reasons that led to research on the topic, chapter 2 examines the current definition of performance and the explanation ofefficient breach theory, establishing its requirements of application in the Common Law, and addressing some of its criticisms. Following, chapter 3 address the concept of contract as an economic operation and the specificities of contracts between companies which demand theneed for selective application of some rules to them. Also the paper address some concepts of Law and Economics focused on the efficient breach theory. In chapter 4, the central theme of this study, will be analyzed the potential barriers to apply the theory under Brazilian law.Furthermore will be analyzed the possibility of applying the theory. For closure, the last chapter presents the conclusions reached through the research, indicating the relevant points on the of the efficient breach theory and answering to the main question whether it is possible to applythe theory in Brazil, under what circumstances and to what extent.